Validation Student Well Being’s Scale for College Students - Febrieta, Ditta; Merida, Sarita Candra (PROCEEDING SERIES OF PSYCHOLOGY, 2024)
Research related to well-being is continuously developing. The construct of well-being in the realm of positive psychology is quite developed, including authentic happiness or happiness, psychological well-being, subjective well-being, or student well-being. student well-being, refers to the ability of students to align demands from within and from the environment which is characterized by positive affect or feelings. This study aims to develop a measuring tool for student well-being, especially for college students. The method used is to validate the measuring instrument using content validity and construct validity which aims to ensure that the measuring instrument is in accordance with its measuring objectives. Reliability analysis is also a part of the measurement of the research instrument so that it can be used from time to time. The student well-being scale is built based on 6 dimensions, namely social, emotional, personal, physical, cognitive, and spiritual dimensions. Based on the validation results found 20 valid items with a reliability coefficient of 0.862. Where, the social dimension has a more dominant variation contribution compared to other dimensions in building student well-being.